(untitled) (International Journal of Physiotherapy, 2018)
Background: Rehabilitation for Parkinson’s disease (PD) has not been found to be an effective intervention for primary impairments caused by dopaminergic cell degeneration, such as tremor or bradykinesia. Recent reports have indicated the efficacy of home exercise on ameliorating primary impairments. However, no studies have examined the effects of aerobic rehabilitation for managing primary impairments of PD. This study aimed to examine the effects of a home-based aerobic exercise program on primary impairments in patients with PD. Methods: This study was conducted by before-after design. The study enrolled 25 patients (male: 7, female: 18) with PD. The intervention involved self-directed aerobic exercise performed using a commercially available pedal exercise apparatus. The participants exercised at home for 20 minutes every day, for approximately four weeks. The variables measured were walking speed, stride length, leg muscle strength, and primary impairments of PD including the Unified Parkinson’s Disease Rating Scale Part 3 (UPDRS3) score as well as the maximum distance, total path length, and movement speed in a finger tapping test. Results: A significant improvement was found in the walking speed (p<0.05), UPDRS3 score (p<0.01), total path length (p<0.01). Conclusions: The proposed home-based aerobic exercise program resulted in significant improvement in UPDRS3 scores, finger tapping test results, and ability to walk, suggesting that such an intervention can achieve recovery of primary impairments in PD patients. The present findings indicate that home-based aerobic exercise therapy is effective for primary impairments of PD.